2020
DOI: 10.1021/acs.jpcc.0c10010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Surface Oxygen Vacancy Formation Energy at Metal/Oxide Perimeter Sites: A Systematic Study on Metal Nanoparticles Deposited on an In2O3(111) Support

Abstract: Metal/oxide support perimeter sites can provide unique properties because the local environment on the support surface is changed by the nearby metal. This study modeled perimeter sites when metal nanorods were adsorbed in lieu of nanoparticles on the (111) surface of an In2O3 support. The metal element M was one of Ag, Au, Cu, Ir, Pd, Pt, and Re. Changes in the surface oxygen vacancy formation energy (E Ovac) with nanorod adsorption were evaluated using systematic first-principles calculations under the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“… 49 Hinuma et al showed that manifestation of the electron scavenger effect is determined by the order of the oxide defect level after O removal and the metal work function. 50 Compared to late transition metals typically adsorbed as nanoparticles, fully oxidized group 3, 4, 5 oxides as well as CeO 2 have very large ionization potentials (IPs), or in other words, the valence band maximum is very deep with respect to the vacuum level. However, the IPs become smaller when the cation is reduced.…”
Section: Resultsmentioning
confidence: 99%
“… 49 Hinuma et al showed that manifestation of the electron scavenger effect is determined by the order of the oxide defect level after O removal and the metal work function. 50 Compared to late transition metals typically adsorbed as nanoparticles, fully oxidized group 3, 4, 5 oxides as well as CeO 2 have very large ionization potentials (IPs), or in other words, the valence band maximum is very deep with respect to the vacuum level. However, the IPs become smaller when the cation is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of an anion leaves behind electrons, and part of the charge would be accommodated by the nanorod if the nanorod is an electron scavenger. Charge flow between metal and oxide through work function engineering has been previously proposed, for example by Pacchioni 31 , and demonstrated on various metal nanorods adsorbed on the In2O3 (111) surface 43 . Fig.…”
Section: Relation Between Bader Charge Transfer and Surface Vacancy F...mentioning
confidence: 92%
“…Activation was typically accompanied by transfer of electrons to the nanorod upon anion removal in TiH2, TiN, and Ti2O3, therefore the activation is a result of the electron scavenger effect that was previously reported in oxides. [42][43]…”
Section: Introductionmentioning
confidence: 99%
“…Our study considered the adsorption of metal nanoparticles on an In 2 O 3 slab with a (111) surface, 88 and the metal element, M, was selected from among Cu, Ag, Au, Pd, Pt, Ir, and Re. The M/In 2 O 3 system was modeled as a semiinfinite M nanorod supported on In 2 O 3 (111); similar models have been employed for investigating metal/oxide sites at perimeters and interfaces (Fig.…”
Section: Metal/oxide Perimeter Sites 88mentioning
confidence: 99%
“…The charge transfer in the case of M = Cu, Ag, Au, and the case where O atoms far away from the nanorods were removed has been investigated in our previous reports. 88 Charge transfer from the O-defect sites near the Pd nanorods (blue spheres, highlighted by blue inverted lines) onto the Pd nanorods can be observed. Similar results were obtained for Ag and Au, and the amount of charge transfer from the support to the nanorod qualitatively becomes larger in the order Ag, Au, and Pd, which means that more charge is transferred from the support site to the metal nanorod when the WF of the metal is larger.…”
Section: Metal/oxide Perimeter Sites88mentioning
confidence: 99%